1996
DOI: 10.2337/diacare.19.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Diabetic Vascular Complications

Abstract: Long-term vascular complications still represent the main cause of morbidity and mortality in diabetic patients. Although prospective randomized long-term clinical studies comparing the effects of conventional and intensive therapy have demonstrated a clear link between diabetic hyperglycemia and the development of secondary complications of diabetes, they have not defined the mechanism through which excess glucose results in tissue damage. Evidence has accumulated indicating that the generation of reactive ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
1,070
9
34

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,670 publications
(1,138 citation statements)
references
References 13 publications
25
1,070
9
34
Order By: Relevance
“…Hyperglycemia-induced ROS production (in the mitochondria) occurs in endothelial cells and in platelets through auto-oxidation of glucose [Wolff and Dean, 1987], advanced glycation end (AGE) product formation and the binding of AGEs to their receptors [Yan et al, 1994;Ceriello, 1999], increased substrate flux through the polyol pathway [Giugliano et al, 1996], and/or through stimulation of the eicosanoid metabolic pathways [Tesfamariam and Cohen, 1992a,b;Quilley and Chen, 2003]. The major sources of O 2 À in cardiovascular cells are: NADH/NADPH oxidase [Griendling et al, 2000], which transfers electrons from NADH or NADPH to molecular oxygen, producing O 2 À ; xanthine oxidase [Wolin, 1996]; endothelial nitric oxide synthase [Ignarro et al, 1999]; cyclooxygenase-2 [Adeagbo et al, 2003]; myeloperoxidase [Berliner and Heinecke, 1996]; and lipoxygenases [Kunsch and Medford, 1999].…”
Section: Oxidative Stress and Diabetesmentioning
confidence: 99%
“…Hyperglycemia-induced ROS production (in the mitochondria) occurs in endothelial cells and in platelets through auto-oxidation of glucose [Wolff and Dean, 1987], advanced glycation end (AGE) product formation and the binding of AGEs to their receptors [Yan et al, 1994;Ceriello, 1999], increased substrate flux through the polyol pathway [Giugliano et al, 1996], and/or through stimulation of the eicosanoid metabolic pathways [Tesfamariam and Cohen, 1992a,b;Quilley and Chen, 2003]. The major sources of O 2 À in cardiovascular cells are: NADH/NADPH oxidase [Griendling et al, 2000], which transfers electrons from NADH or NADPH to molecular oxygen, producing O 2 À ; xanthine oxidase [Wolin, 1996]; endothelial nitric oxide synthase [Ignarro et al, 1999]; cyclooxygenase-2 [Adeagbo et al, 2003]; myeloperoxidase [Berliner and Heinecke, 1996]; and lipoxygenases [Kunsch and Medford, 1999].…”
Section: Oxidative Stress and Diabetesmentioning
confidence: 99%
“…Increased production of reactive forms of oxygen and lipoperoxides together with lowered levels of substances (vitamin C, vitamin A, lipoic acid, glutathione) having antioxidative reaction and enzymes acting as antioxidative agents such as superoxide dismutase and catalase can be found in the blood and tissues of patients affected with the disease (7). According to the current views, the antioxidative stress plays a significant role in the etiopathogenesis of diabetes mellitus of both first and second types and has key importance in the occurrence and development of diabetic complications (8).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports [13][14][15] found an increased 8-OHdG level in mononuclear cells and urine in patients with insulin-dependent diabetes mellitus (IDDM) and non-insulin-dependent diabetes mellitus (NIDDM). Giugliano et al [16] reported that the leukocyte or urinary 8-OHdG was related significantly with the severity of diabetic nephropathy and retinopathy. The study of Hinokio et al [17] provided direct evidence that increased urinary 8-OHdG at entry was associated with the development of diabetic nephropathy after 5 years.…”
Section: Introductionmentioning
confidence: 99%